(untitled) (Journal of the College of Basic Education, 2022)
This research summarizes the importance of the environmental reference in the expressive ability of the architectural sculpture, as it is one of the most important references that affects, in whole or in part, the style of construction and the patterns of synthesis of data and forms in the structural composition. Some compressed axes were tabbed to clarify the most important concepts related to the environmental reference and sculptural architecture, as well as the concept of expression in architectural sculpture. The UAE was adopted as a community for research samples, from which three samples were taken according to the mechanism adopted in the research.